Bibliometric Analysis of the Development of Islamic Economic Dispute Resolution Research in Indonesia - Erie Hariyanto; Moh. Hamzah (Institut Agama Islam Negeri Batusangkar, 2022)
This research aims to explore the development of scientific publications in the field of sharia economic dispute resolution from 2017 to 2022, this year was chosen because three conditions occurred in that year, namely before, during and after or began to subside the Covid-19 pandemic. Thus, the results of this study will have an impact on policy making and become material for future research and use by policy makers in the field of sharia economic dispute resolution. There are two formulations of the problem to be answered, namely: 1) How is the development of scientific publications in the field of sharia economic dispute resolution in Indonesia from 2017 to 2022. 2) What is the existence of scientific publications in the field of sharia economic dispute resolution in the Islamic economic order in Indonesia. Research which is a type of library research, researchers will use a bibliometric approach method with data presentation techniques that are descriptive quantitative in nature. The results of this study are: First, the development of scientific publications from 2017 to 2022 in the field of Islamic economic dispute resolution has fluctuating results (not fixed), with a total of 1001 publications with the highest peak occurring in 2021 and the lowest point occurring in 2017 and there are 12 productive researchers. Second, the existence of scientific publications in the field of sharia economic dispute settlement has an important role in social life, where the results of these publications are used as evaluation material or material for finding solutions for Islamic financial institutions in resolving sharia economic disputes and become an important study in impacting policy makers. in decision-making in the field of sharia economic dispute resolution.